Predictions of the Climate Change-Driven Exodus of the Town of Tangier, the Last Offshore Island Fishing Community in Virginia's Chesapeake Bay - Wu, Zehao; Schulte, David (Frontiers in Climate, 2021)
Sea-level rise (SLR) has been confirmed to be accelerating globally due to climate-change driven human influence. Multiple studies suggest many coastal communities will soon be inundated by SLR. Prior to inundation, habitable uplands above the high tide line first convert to uninhabitable wetlands, forcing human exodus. Habitability, not the land’s presence above the low tide line, drives exodus. We determined the time left for uplands of the Town of Tangier of VA, USA to be converted to wetlands, analyzed local sea level rise data to determine the best local SLR scenario (low, mid, or high) fit, then compared upland conversion rate to the rate of population decline. The upland landmass constituting the Town of Tangier declined from 32.8 HA to 12.5 HA (1967-2019), accelerating over time, with complete conversion to wetlands predicted by 2051. The US Army Corps of Engineers (USACE) high SLR curve is the best fit to the local tide gauge’s raw data (1967-2020), indicating local sea level rise has rapidly accelerated in recent decades, concomitant with the rate of wetland conversion. The Town’s population, declining since the 1930s, accelerated rapidly after 1980, trending downward in tandem with the conversion of the Town’s uplands to wetlands. We estimated costs to relocate the Town as well as for a conceptual plan to provide long-term stability to the Town and Island of Tangier.